Everolimus in the treatment of metastatic thymic epithelial tumors. (November 2020) - Hellyer, Jessica A.; Ouseph, Madhu M.; Padda, Sukhmani K.; Wakelee, Heather A.
Highlights: Everolimus demonstrated efficacy in a real-world cohort of advanced thymic tumors. Everolimus has expected and manageable toxicities in patients with thymic tumors. Pathogenic mutations were found in 27 % of patients and included TP53 and CDKN2A. Abstract: Introduction: There is emerging evidence to support the use of mTOR inhibitor everolimus in patients with advanced, relapsed-refractory thymic epithelial tumors (TETs). However, patient selection and identifying predictive biomarkers of response remains a challenge. Here, we describe a single-center experience with everolimus in patients with TETs and provide detailed molecular analysis of their thymic tumors. Materials and Methods: Data on all patients with advanced TETs who were prescribed everolimus at Stanford University were retrospectively assessed. Time to treatment failure (TTF) and overall survival (OS) were calculated. STAMP, a 130-gene targeted next generation sequencing (NGS) panel, was performed on each tumor sample. Results: Twelve patients with thymoma (T) and three with thymic carcinoma (TC) treated with everolimus were included. Patients had been heavily pre-treated with an average of three prior lines of therapy. Three patients discontinued treatment due to adverse events. The average TTF was 14.7 months in T and 2.6 months in TC with median OS of 27.6 months in the entire cohort (NR T and 5.3 months TC). Two patients with paraneoplastic autoimmune diseases had improvement in autoimmunity on everolimus. Pathogenic mutations were observed in 4/15 (27 %) of patients and included TP53, KEAP1 and CDKN2A . Several variants of unknown significance in key genes responsible for modulating tumor response to mTOR inhibition were also found. Conclusion: As previously reported in a prospective trial, patients with previously treated advanced TETs appear to benefit from everolimus in this single institution cohort. Moreover, there was a manageable toxicity profile and no cases of everolimus-induced pneumonitis. A targeted NGS panel revealed several pathogenic mutations but there was no association between detectable tumor mutations and time to treatment failure in this cohort.